2020
DOI: 10.3390/genes11091101
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Genome Instability and Determinants of Mutational Landscape in Cancer Cells

Abstract: Genome instability is a crucial and early event associated with an increased predisposition to tumor formation. In the absence of any exogenous agent, a single human cell is subjected to about 70,000 DNA lesions each day. It has now been shown that physiological cellular processes including DNA transactions during DNA replication and transcription contribute to DNA damage and induce DNA damage responses in the cell. These processes are also influenced by the three dimensional-chromatin architecture and epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…This may occur not only because pro-inflammatory and oncogenic pathways often overlap but also because inflammation induces tissue damage and repair attempts and is interconnected with the production of high levels of ROS. These molecules are able to promote genomic instability that may increase the probability that onco-suppressors, such as, for example, p53, or proteins involved in DNA damage repair pathways, such as BRCA1, undergo loss-of-function mutations [ 45 ]. In the present study, we found that HHV-6A was able to infect BCPAP, a cell line derived from well-differentiated papillary thyroid carcinoma (PTC), the most benign form of thyroid cancer, and induce several effects that could favor progression towards more aggressive forms of thyroid cancers such as FTC or ATC.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur not only because pro-inflammatory and oncogenic pathways often overlap but also because inflammation induces tissue damage and repair attempts and is interconnected with the production of high levels of ROS. These molecules are able to promote genomic instability that may increase the probability that onco-suppressors, such as, for example, p53, or proteins involved in DNA damage repair pathways, such as BRCA1, undergo loss-of-function mutations [ 45 ]. In the present study, we found that HHV-6A was able to infect BCPAP, a cell line derived from well-differentiated papillary thyroid carcinoma (PTC), the most benign form of thyroid cancer, and induce several effects that could favor progression towards more aggressive forms of thyroid cancers such as FTC or ATC.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated DNA synthesis has been linked to human diseases including cancer 14 16 . Indeed, a subset of RECQ4 clinical mutations are tumorigenic 3 , making RECQ4 an ideal candidate to study the contribution of DNA synthesis dysfunction to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic instability, one of the most prevalent features of human cancers, can cause cells to exhibit the cancer phenotype through mutations in oncogenes and cancer suppressor genes (3). Persistent genomic instability allows cancer cells to survive under selective pressure and adapt to their microenvironment by evolving to resist different therapies (4), and affects patient prognoses (5). Although genomic instability can promote cancer development and drug resistance, it can cause cancer cell death when genomic instability continues to increase to a limiting level; thus, genomic instability has therapeutic potential for treating cancer (5)(6)(7), and elucidating the specific regulatory mechanisms involved is of great significance.…”
Section: Introductionmentioning
confidence: 99%